Postoperative day one systemic inflammatory response syndrome is a powerful early biomarker of clinically relevant pancreatic fistula. Issue 1 (January 2023) - Ausania, F.; Gonzalez-Abós, C.; Martinez-Perez, A.; Arrocha, C.; Pineda-Garcés, C.; Landi, F.; Fillat, C.; Garcia-Valdecasas, J.C.
Abstract: Background: Clinically relevant postoperative pancreatic fistula (CR-POPF) is the most feared complication following pancreaticoduodenectomy (PD). There is increasing evidence that very early postoperative factors can be helpful to identify high-risk patients. The aim of this study is to analyze whether postoperative day one (POD1) systemic inflammatory response can be used as an early biomarker of CR-POPF development. Methods: All patients undergoing PD from 2014 to 2020 were considered. Variables were extracted from a prospectively held database. Clinical and perioperative variables, including POD1 systemic inflammatory response syndrome (SIRS) and C-reactive protein level were collected. To elucidate the independent role of early CR-POPF biomarkers, multivariate hierarchical logistic regression analyses were planned. Results: Out of 243, 213 patients were included in this analysis. CR-POPF occurred in 49 (23.0%) patients and 90-day mortality was 1.4%. POD1 SIRS was reported in 65 (30.5%) patients. Following hierarchical logistic regression analyses, CR-POPF was independently associated with body mass index (OR = 2.787, p = 0.003), soft pancreatic texture (OR = 4.258, p = 0.002) and POD1 SIRS (OR = 50.067, p = 0.001). Conclusion: POD1 SIRS is powerfully associated with CR-POPF and therefore it could be used as a tool to optimize postoperative care of PD patients. Further prospective studies are needed to validate these findings.